Linezolid resistance in patients with drug-resistant TB and treatment failure in South Africa - Wasserman, Sean; Louw, Gail; Ramangoaela, Limpho; Barber, Garrick; Hayes, Cindy; Omar, Shaheed Vally; Maartens, Gary; Barry, Clifton; Song, Taeksun; Meintjes, Graeme (Journal of antimicrobial chemotherapy, 2019)
Limited data exist on clinical associations and genotypic correlates of linezolid resistance in Mycobacterium tuberculosis. We aimed to describe mutations and clinical factors associated with phenotypic linezolid resistance from patients with drug-resistant TB at two public sector facilities in South Africa. Adults and adolescents with treatment failure (culture positivity ≥4 months) on a linezolid-containing regimen were retrospectively identified. Phenotypic resistance, as defined by a linezolid MIC >1 mg/L, was assessed for retrieved isolates using broth microdilution. Targeted sequencing of rrl and rplC was performed, irrespective of growth on subculture. Thirty-nine patients with linezolid-based treatment failure were identified, 13 (33%) of whom had phenotypic or genotypic linezolid resistance after a median duration of 22 months (range = 7-32) of linezolid therapy. Paired MIC testing and genotyping was performed on 55 unique isolates. All isolates with phenotypic resistance (n = 16) were associated with known resistance mutations, most frequently due to the T460C substitution in rplC (n = 10); rrl mutations included G2814T, G2270C/T and A2810C. No mutations were detected in isolates with MICs at or below the critical concentration. Linezolid resistance occurred in a third of patients with drug-resistant TB and treatment failure. Resistance occurred late and was predicted by a limited number of mutations in rrl and rplC. Screening for genotypic resistance should be considered for patients with a positive culture after 4 months of linezolid therapy in order to optimize treatment and avoid the toxicity of ineffective linezolid therapy.